Normal Humeral Head Ossification in Pediatric and Adolescent Shoulders Can Mimic Hill-Sachs Lesions: A Magnetic Resonance Imaging–based Study. Issue 2 (February 2022) - Kelly, Alexander; Heath, Madison R.; Amoroso, Elizabeth E.; Mackie, Alexandra T.; Greditzer, Harry G.; Owens, Brett D.; Fabricant, Peter D.
Abstract : Background: The sequential maturation of the humeral head (HH) as viewed on magnetic resonance imaging (MRI) has not been described to date. Proper assessment may be complicated by the presence of physeal tissue in pediatric patients. Past studies suggest that skeletally immature patients may also have a higher risk of a false-positive diagnosis of Hill-Sachs lesion on MRI. The purpose of this study was to define pediatric HH developmental patterns using MRI and to investigate for any associations with findings of known false-positive Hill-Sachs. Methods: Picture Archiving and Communication System (PACS) records at an urban academic tertiary care musculoskeletal facility from 2014 to 2020 were queried for shoulder MRI in patients aged 0 to 15 years. Patients were excluded if they had a history of glenohumeral instability, fracture, growth arrest, brachial plexus injury, surgery, or infection. All images were independently evaluated by a musculoskeletal fellowship-trained radiologist. Each HH was staged based on skeletal maturity. Results: For both sexes, HHs matured in a predictable manner with increasing chronological age associated with a higher ossification stage. False Hill-Sachs lesions were observed in girls aged 4 to 7 and boys aged 5 to 14, exclusively during stage I to II ossification. Conclusions: False Hill-Sachs lesions were visualized on MRI in stage I to II proximal humerus ossification. Due to differential timing of skeletal maturation, males present with false Hill-Sachs lesions at a later age than females on average. When interpreting shoulder MRI for glenohumeral instability, clinicians should be cautious of false Hill-Sachs lesions, especially in younger patients with distinct greater tuberosity and HH ossification centers (stage I to II ossification). Level of Evidence: Level III.